Pembuatan Aplikasi Pembelajaran Aksara Sunda Di SDN Griya Bandung Indah - Galih Ashari Rakhmat; Muhamad Rizal S; Muhamad Fathan A; Muhamad Fazly (Jurnal Pelayanan Hubungan Masyarakat, 2023)
REKA KARYA: In this era of globalization, Indonesia is not immune to its influence, which can potentially erode traditional cultural values and replace them with Western culture. To address this concern, the Pengabdian Masyarakat program aims to help Sundanese language teachers by developing a Sundanese script learning app. By doing so, it is hoped that students will become more interested in learning about the Sundanese script. The app will include a program flow design, display design, quiz/game design, and database design. Additionally, it will feature a quiz menu in the form of a game to help users practice their Sundanese script skills. The goal is to create a user-friendly and engaging app that is accessible to everyone who wants to learn the Sundanese script.